Isolation and possible relevance of Thermoactinomyces candidus proteinases in farmer's lung disease. - Roberts, R C (1983)
The thermophilic actinomycetes are the most common etiological agents causing hypersensitivity pneumonitis. Antigen preparations of these organisms contain proteolytic activity. Further investigation of the proteinases of the thermophilic actinomycetes was undertaken to determine whether this activity may contribute directly to the pathogenesis of hypersensitivity pneumonitis and pulmonary mycotoxicosis. The presence of proteolytic activity in aerosolized dust from moldy silage was demonstrated, and antibodies to two proteolytic enzymes from Thermoactinomyces candidus were found in the blood of farmer's lung patients who had been sensitized to this organism. These two enzymes were isolated from culture filtrate antigen preparations that had been partially characterized with respect to the proteolytic activities and their interaction with human serum proteinase inhibitors. Both proteinases belonged to the serine class of endopeptidases. Neither proteinase was inhibited by alpha 1-proteinase inhibitor or alpha 1-antichymotrypsin. Both proteinases were inhibited by alpha 2-macroglobulin. One of the proteinases had elastase activity. Inhalation of these proteinases apparently does occur, and they may induce an inflammatory response in the lungs since they are not inhibited by the main proteinase inhibitors protecting the lung.